Relationship between Caregiver Behavior in Young Child Feeding Practice Among Children Aged 12-23 Months with Stunting at Suburban Area Jatinangor West Java - Indonesia (Morressier, 2017)
Background. Stunting is malnutrition condition caused by unfulfilled nutrition for a long period. Stunting can be reduced by one of factor that affect the fulfillment of nutritional requirement, which is caregiveru2019s behavior in feeding practices.Objective. To know association between caregiveru2019s behavior in young child feeding practices with stunting.Methods. This cross sectional study was participated by mothers and children aged 12-23 living in the working area of Jatinangor Primary Health. Data collected by interview using questionnaire based on guideline from Ikatan Dokter Anak Indonesia (IDAI) and World Health Organization (WHO). Child measured by infantometer. Statistical analysis using chi square and Mann Whitney test. Result. This study collected 217 subjects with 59 of them (27.2%) are stunted. P value for adequate feeding and responsive feeding are 0.003 and 0.012, respectively. P value for timely and safe feeding are more than 0.05. Overall, caregiveru2019s behavior in child feeding practice showed p<0.05. Conclusion. There is association between child feeding practice and stunting. Adequate and responsive feeding practice showed a relationship with stunting, meanwhile safe and timely feeding show no relationship with stunting.